Evaluation of the retinal ON- and OFF-responses in the dog ERG - Kristensson, Charlotte (SLU/Dept. of Clinical Sciences (until 231231), 2014)
The aim of the study was to examine the retinal ON- and OFF-pathways of the canine electroretinogram (ERG). The ON- and OFF-pathways are used to distinguish objects from their backgrounds. A dark object is discernible from a lighter background using the OFFpathway and the ON-pathway is used to descry a light object upon a darker background. This study shows that the dog ERG has both ON- and OFF-responses and that these responses can be separated by prolonging the flash duration over 50 ms. The dog OFF-response waveform was more similar to the cat OFF-response than the human OFF-response (Frishman, 2006; Zrenner and Gouras, 1979). In this study six female three-year-old Beagle dogs were included. Both background and flash stimuli were provided by LEDs (light emitting diodes) with a wavelength of 470 nm, a wavelength that is absorbed almost as effectively by the canine M/L-cones as by the S-cones. These stimuli gave ERGs with both ON- and OFF-responses. It was found that a background intensity of 40-60 cd/m2 provided good ERGs with a-waves, distinct b-waves and a small positive OFF-response followed by an obvious negative OFF-response. When the relative flash intensities were varied from 12.28 to 12.8 log relative photons/m2 per 100 ms- flash, all three curves were clearly readable. Flash intensities exceeding 12.8 log relative photons/m2 reduced the negative OFF-response amplitudes. Additional examinations ought to be made to gain knowledge about the OFF-responses of the S- and M/L-cones, respectively. This study also warrants further investigations on the cellular origin of the canine OFF-response, in particular the late negative OFF-component.